Blogger Independent news Jurnalist - Mufadhol Mufadhol (Dinamik, 2009)
Blog represent revolution new information and nowaday. Blogger is the one News journalist whichremain when a country in charge sensor especial media. Ethics of Pers journalistic that is correctness,accuration, sincerity, transparent and freedom. Most blog consist of news and renewed (update) routinelyin the form of managed diary by using interaktif desain and can be commented by visitor. One of  providerof free blog is blogsome.com.